Clinical glycomics in the diagnostic laboratory - Post, Merel A.; Lefeber, Dirk J. (Annals of Translational Medicine, 2019)
Glycosylation is the most diverse type of protein modifications. Glycosylation occurs in the endoplasmatic reticulum (ER) and Golgi apparatus. The presence of multiple competing glycosyltransferases and glycosidases results in a highly heterogeneous population of glycan structures on each protein.